Perawan Remaja yang Dilupakan: Studi Kasus Jugun Ianfu pada Masa Pendudukan Jepang di Indonesia 1942-1945 - Farisa, Pawit Fadila Rika; Ketaren, Saher Remal Agungta; Dwiastuti, Winda; Rafie, Mohammad Thoriq Zadien; Setiawan, Panji Ahmad; Amelia, Sindy Meriahni; Widyaardana, Febrian (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
The Japanese occupation of Indonesia (1942–1945) was marked by extensive exploitation of human and natural resources, including the practice of Jugun Ianfu, a system of sexual slavery enforced by the Japanese military. This practice involved the forced recruitment of women, including minors, to serve in military barracks (ianjo) under the pretext of maintaining troop morale. Influenced by the ideology of Hakkō ichiu and military health concerns, this policy caused severe physical and psychological trauma to the victims. Using historical and normative methods, this study analyzes the victims' vulnerabilities, social and psychological impacts, and international legal frameworks on compensation rights. Findings reveal that this systematic war crime violated human rights, with victims entitled to reparations under international law.